Critical phenomenon of the layered chiral helimagnetic YbNi3Al9. (20th January 2020) - Wang, Yamei; Liu, Wei; Zhao, Jun; Fan, Jiyu; Pi, Li; Zhang, Lei; Zhang, Yuheng
Abstract: Two-dimensional layered YbNi3 Al9 exhibits a chiral helimagnetic ground state, which is a candidate for the field-modulated chiral magnetic soliton. In this work, the magnetism and critical phenomenon of YbNi3 Al9 are investigated. As H ⊥ c, a magnetic step with loop can be observed in the field-dependent magnetization, which may be corresponding to the possible chiral magnetic soliton phase transition. Based on the analysis of isothermal magnetization around T C, the critical exponents are obtained as β  = 0.1370(2), γ  = 1.7955(4), and δ  = 14.1043(7), which fulfill the Widom scaling relation and Rushbrooke's law. Moreover, the obtained critical exponents are testified by the modified Arrott plot and scaling hypothesis. The critical exponents of YbNi3 Al9 are close to the theoretically prediction of 2D-Ising model with the spatial-dimensionality n  = 2 and spin-dimensionality d  = 1, indicating one-dimensional magnetic coupling in the two-dimensional framework. Based on universality scaling, we construct the detailed H – T phase diagram around the phase transition with H ⊥ c, which reveals that the field-induced magnetic transition for H ⊥ c is of the first-order type.